Щодо питання аналізу та оцінки фінансової діяльності підприємства в сучасних умовах - Єршова, Наталя Юріївна; Терземан, М. М. (НТУ "ХПІ", 2011)
In article methodical approaches to the analysis both financial results and an estimation of a financial condition of the enterprises are considered. The groups of administrative problems connected with increase of financial stability of the enterprises are formulated. Stages of carrying out of the analysis of a financial condition of the enterprise that will allow to carry out the proved choice of methods of financial improvement of the enterprise are offered.
Keywords: результати фінансові; проблеми управлінські; стабільність фінансова; підходи методичні